Masticatory performance, self-perception of oral health, oral health-related quality of life and nutritional status of completely edentulous elderly patients submitted to different rehabilitation treatments: A cross-sectional study - Jabr, Camila Luiz [UNESP]; Oliveira, Lucas Portela [UNESP]; Pero, Ana Carolina [UNESP]; de Assis Mollo Júnior, Francisco [UNESP]; Filho, João Neudenir Arioli [UNESP] (Wiley, 2024)
Background: The impact of treatments on completely edentulous individuals on masticatory performance (MP), oral health-related quality of life (OHRQoL), nutritional status (NS) and socio-economic profile (SP) is unclear in the literature. Objective: To compare the MP, OHRQoL, NS and SP of totally edentulous elderly users of bimaxillary complete dentures (CD) and users of lower implant-supported fixed complete dentures (IFCD). Methods: Forty participants were allocated into groups according to rehabilitation treatment (n = 20): bimaxillary CD (G1) and lower IFCD, and upper CD (G2). The evaluation of MP used almonds by the method of sieves. Four questionnaires (Geriatric Oral Health Assessment Index–GOHAI and Oral Health Impact Profile Edent–OHIP-Edent, Brazilian Economic Classification Criteria–ABEP and Mini Nutritional Assessment-MNA) were applied to assess the OHRQoL, SP and NS of the elderly, respectively. After evaluating the statistical assumptions, the Mann–Whitney (α =.05) test was applied to compare the groups regarding MP, OHRQoL, NS and SP. Spearman's correlation (α =.05) was performed to verify the correlation between the MP, the OHRQoL and the NS of the participants. Results: G2 showed better MP (p <.05) in all masticatory cycles, OHRQoL (p <.05) and NS than the G1. However, the participants' self-perception of oral health did not differ between groups (p <.05). A moderate negative correlation was found between MP and OHRQoL for 40 masticatory cycles (r2 = −0.513; p =.001). Conclusion: Individuals rehabilitated with IFCD had a higher average monthly family income and achieved superior behaviour in MP and OHRQoL, in addition to lower risks of malnutrition when compared to individuals using bimaxillary CD.
Keywords: chewing; edentulous arcade; elderly; nutritional status; quality of life